The turnover of myelin phospholipids in the adult and developing rat brain - Jungalwala, F. B. (1971)
1. Inorganic [(32)P]phosphate, [U-(14)C]glycerol and [2-(14)C]ethanolamine were injected into the lateral ventricles in the brains of adult rats, and the labelling of individual phospholipids was followed over 2–4 months in both a microsomal and a highly purified myelin fraction. 2. All the phospholipids in myelin became appreciably labelled, although initially the specific radioactivities of the microsomal phospholipids were somewhat higher. Eventually the specific radioactivities in microsomal and myelin phospholipids fell rapidly at a rate corresponding to the decline of radioactivity in the acid-soluble pools. 3. Equivalent experiments carried out in developing rats with [(32)P]phosphate administered at the start of myelination showed some persistence of phospholipid labelling in the myelin, but this could partly be attributed to the greater retention of (32)P in the acid-soluble phosphorus pool and recycling. 4. It is concluded that a substantial part of the phospholipid molecules in adult myelin membranes is readily exchangeable, although a small pool of slowly exchangeable material also exists. 5. A slow incorporation into or loss of labelled precursor from myelin phospholipids does not necessarily give a good indication of the rate of renewal of the molecules in the membrane. As presumably such labelled molecules originate by exchange with those in another membrane site (not necessarily where synthesis occurs) it is only possible to calculate the turnover rate in the myelin membrane if the behaviour of the specific radioactivity with time of the phospholipid molecules in the immediate precursor pool is known.